An exploration of factors that influence referrals to palliative care in oncology - Matsiliza, Nosisa C (Department of Medicine, 2025)
Background: Globally, cancer is a leading cause of death. The impact of cancer is higher in low-middle income countries, compared to middle-high income countries. In Africa, the WHO projects a 403% increase in cancer between 2016 and 2060. There is convincing evidence that there are benefits to patients in providing palliative care together with oncology treatment. These benefits include understanding of prognosis, improvement in quality of life, and an increase in satisfaction with care for the patients. However, in South Africa, there is a paucity of early referrals to palliative care. Aim: The aim of the study was to determine factors that influence referral of patients with cancer, to palliative care services. Methods: This was a qualitative cross-sectional study allowing for in-depth exploration of participants' views. There were two groups of participants 1) adult patients diagnosed with cancer, and already informed of their diagnosis; 2) medical and radiation oncologists. Purposive sampling was undertaken with planned sample size of 10-14 patient participants and 8-10 oncologist participants The participants were fully informed regarding the research and asked to sign consent to take part in the research. In depth interviews were conducted following interview guides – for patients and for oncologists. Thematic analysis was conducted manually by the researcher with the support of the supervisor, and themes derived from transcripts of the participants' interviews. Results: Participants were twelve patients with cancer and eight practising oncologists. Five major themes were identified: 1) Experiences of care; 2) Relationship between oncology and palliative care; 3) Patient views on referral to palliative care services; 4) triggers for referral to palliative care services; 5) Practical considerations in referral to palliative care services. Key findings were the need for good effective communication, providing enough information to enable patients to make informed choices, a need met by palliative care services but not by oncologists whose communication manner was hurtful, without compassion and empathy and left patients unclear or overwhelmed. There is a difference in the understanding of palliative care by oncologists, while patients saw a need for early referral to palliative care services. Conclusion: The quality of life in patients with advanced cancer is negatively affected by oncologists' lack of effective communication. These patients, referred late to palliative care services, remain with unmet information needs. However, they are highly appreciative of palliative care services even when they are referred to these services near the end of their lives. Patients with advanced cancer may benefit more with early referral to palliative care services, while oncologists' communication skills and understanding of what palliative care is, may benefit from palliative care training.